(untitled) (International Journal of Food and Nutritional Sciences, 2022)
There is no doubting the fact that the family is and always will be the most important factor in determining the quality of life that is both the richest and the most meaningful for humans. The coming together of two people who were raised in separate environments to share a home and raise children results in the formation of a family. Marriages that are successful demonstrate the capacity of the pair to acknowledge one other’s flaws while simultaneously celebrating their strengths. The majority of people’s social lives revolve on their families, making the family unit not only the incubator of our emerging society but also the centre of their social lives. Ordinary men and women place a high value on their homes and families as a cornerstone of their aspirations and sense of self-respect. Everyone, regardless of age, may find the utmost solace and support within the context of their family. The majority of individuals get their primary feeling of accomplishment from being able to successfully bring up a family. The happiness and sadness that are experienced inside one’s own family are, respectively, the ones that are felt the most intensely by the majority of men and women. Marriage may provide support, safety, combined resources, shared household assets, sexual and emotional connection, and assistance with day-to-day obligations. These are a few ways that marriage might enhance a person’s well-being and life satisfaction. Divorce is a frequent outcome of marital discontent and may occur in any kind of union. Divorce may have lasting negative consequences. The goal of premarital and marriage counselling is to reduce marital strife and enhance marital pleasure. Can being married or in a relationship suffice for eligibility? The research investigated the relationship between marital satisfaction and various measures of well-being. The disparities in well-being between married or in a relationship and single persons, as well as between the sexes, were also investigated. The poll includes 1087 Croatian adult Internet users. The general well-being, marriage and relationship satisfaction, and demographic information of the subjects were analysed. The MRS was slightly associated with all well-being factors, although it was most strongly connected to love life and family ties. Those who were married or in a committed relationship had a higher MRS than those who were single.